Morphometric and Functional Characteristics of Buffaloes and Cows Corpus Luteum at Different Stages of the Estrous Cycle - Leal, Luciana; Oba, Eunice [UNESP]; Moya-Araujo, Carla; Prestes, Nereu [UNESP] (Int Buffalo Information Ctr, 2013)
The aims of the present study were to evaluate the morphometry of corpus luteum (CL) and progesterone (P-4) plasma concentration of 86 buffaloes (33 pregnant and 53 non-pregnant) and 95 cows (36 pregnant and 59 non-pregnant) at the moment of slaughter. Seventy CLs of buffaloes and 110 CL of cattle were analyzed. The CL classified as II and III were more common in both species (35.7 and 41.4% for buffaloes and 43.6 and 35.5% for cows). The 29 non-pregnant buffaloes had a total of 36 CL, being 19.4% CLI; 33.3% CL II; 27.8% CL III and 19.4% CL IV. The 51 nonpregnant cows had a total of 71 CL, being 26.8% CL I; 47.9% CL II; 21.1% CL III and 4.2% CL IV. The average diameters of bubaline and bovine CL were 5.2 +/- 0.9 and 6.4 +/- 1.8 mm (CL I); 17.6 +/- 2.6 and 19.8 +/- 3.2 mm (CL II); 17.2 +/- 2.1 and 20.0 +/- 3.2 mm (CL III); 7.8 +/- 1.8 and 8.7 +/- 2.7 mm (CL IV), respectively. The mean plasma concentrations of P4 were 5.6 (CL I); 5.4 (CL II); 4.7 (CL III) and 0.5 (CL IV) ng/mL for buffaloes and 0.02 (CL I); 6.3 (CL II) and 6.4 (CL III) ng/mL for cows. In both species, P4 concentration was similar between stages II and III. The results indicated that the characterization of the CL provides important information about the status of estrous cycle.
Keywords: Corpus luteum; Progesterone; Buffaloes; Cows